A structure-based activity study of highly active unsymmetrically substituted NHC gold(I) catalysts - Zargaran, Poorya; Wurm, Thomas; Zahner, David; Schießl, Jasmin; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2018)
Following the modular template synthesis using isonitriles, new unsymmetrically substituted five-membered saturated N-heterocyclic carbene (NHC) and N-heterocyclic oxo-carbene (NHOC) gold(I) complexes were prepared. With these species and already reported complexes, a detailed study concerning the catalytic activities of the complex classes available by the isonitrile route was conducted. The catalytic properties of twelve different types of NHOCs, saturated and unsaturated NHC gold(I) pre-catalysts with different substituents, as well as one representative of a six-membered NHC and one N-acyclic carbene (NAC) gold(I) complex were analyzed by utilizing the phenol synthesis as a test reaction. For this reaction, the saturated NHC gold(I) complexes achieved higher conversions than the corresponding unsaturated NHCs and the NHOC systems. While unsaturated NHC complexes show higher catalytic activity during the initial phase of the conversion, due to a higher stability, higher turnover numbers (TONs) were obtained for the corresponding saturated systems. A cyclopentadecyl substituent at nitrogen turned out to be the privileged substituent for all of the unsymmetrical complexes. Furthermore, we detected that light exclusion can significantly increase the catalytic activity of NHC gold(I) complexes for phenol synthesis.